DEMOCRACY IN THE CONTEXT OF MATERIAL SHORTAGE IN NIGERIA’S FOURTH REPUBLIC: LIMITATIONS AND THE WAY AHEAD - Akhakpe, Ighodalo (European Scientific Journal, ESJ, 2013)
Virtually all modern independent States have as their fundamental goals the pursuit of the welfare and well-being of their citizens. To achieve these goals, the Nigerian State is required to harness its huge human and material potentials for the development of the country. This encompasses increase in employment generation, and improvement in literacy and health status as may be found in longevity and social stability. For several decades all these could not be realized due to bad governance under militarily authoritarian rule. With the inauguration of civilian rule in 1999, it was expected that democratic rule will stem the tide of economic decline and socio-political instability. Over a decade the country is still groaning under socio-economic and political miseries. With the use of political participation theory, the paper argued that the only practical way to surmount the present material shortage is to empower a person to make informed choices and contribute actively in making public decisions which affects their welfare and well-being to recreate their environment and unleash their innate potentials for self development and corporate co-existence. All these involve breaking with the tragedy of the past and increasing the likelihood of achieving the goals of a wealthier, healthier and better educated citizenry under democratic rule.